Effect of Different Methods of Processing and Antioxidant Supplementation on the Storage Quality of Hatchery Waste Meal - Mahmud, Athar; Saima; Hayat, Zafar; Ullah Khan, Muhammad Zafar; Basheer, Atia; Zahoor, Imran (Pakistan Journal of Nutrition, 2014)
Four different levels of antioxidant (Oxygun®) at 0, 100, 200 and 300 mg/kg were added to the ground, processed viz, cooked, autoclaved, extruded and raw hatchery waste. Samples were stored for 50 days and analyzed for peroxide value (PV), thiobarbituric acid value (TBA) and free fatty acids (FFA) with 10-days of storage interval. Linear increase was observed in PV, FFA and TBA values of all treatments throughout the storage period. Comparison within raw hatchery waste (RHW), cooked HW, autoclaved HW and extruded HW revealed that extrusion was found to be the most effective processing technique to check fat oxidation, followed by autoclaving and simple cooking whereas unprocessed HW showed maximum fat deterioration. PV, FFA and TBA decreased with all levels of antioxidant addition when compared with control group. Significantly highest (p<0.05) levels of PV, FFA and TBA were observed in control group while least degradation of fat was observed in extruded samples with 300 mg/kg of antioxidant addition. All the processing techniques and antioxidant addition checked the fat rancidity throughout the storage period, compared to control group, however synergistic effect of extrusion and 300 mg/kg of antioxidant addition was found to be most appropriate to keep the samples highly acceptable for 50 days storage period.